Survival after neoadjuvant chemotherapy versus neoadjuvant chemoradiotherapy for resectable esophageal carcinoma: A meta‐analysis. Issue 2 (11th August 2015) - Fan, Mengying; Lin, Yao; Pan, Jianhong; Yan, Wanpu; Dai, Liang; Shen, Luyan; Chen, Keneng
Abstract: Background: The efficacy of surgery alone for patients with locally advanced esophageal cancer (EC) is still unsatisfactory. Presently, induction therapy followed by surgery is the standard treatment. Preoperative chemotherapy (CT) and chemoradiation (CRT) are proven effective induction therapies; however, few sample studies have addressed these treatments, thus, their superiority remains uncertain. We performed a systemic review and meta analysis to test the hypothesis that induction CRT prior to surgery could improve survival compared with induction CT alone. Methods: A comprehensive search of PubMed and the Ovid database for relevant studies comparing EC patients undergoing resection after treatment with induction CT alone or induction CRT was conducted. Hazard ratios (HR) and 95% confidence intervals (95% CI) were extracted from these studies to provide pooled estimates of the effect of induction therapy on overall survival. Results: Five studies met the criteria for analysis. Statistical analysis demonstrated a survival benefit of induction CRT compared with induction CT alone (HR0.73, 95% CI 0.61–0.89; P = 0.002). Further analysis showed that induction CRT perioperative mortality and complication rates were higher than for induction CT alone (HR 2.96, 95% CI 1.38–6.37; HR1.6, 95% CI 1.30–1.98; P = 0.01, respectively). Conclusions: Published evidence comparing the different efficacies of induction CT and induction CRT is sparse, with few samples of adenocarcinoma. This analysis supports the view that, compared with induction CT, induction CRT could achieve a long‐term survival benefit in EC patients.